Assessment of limited downstream nitrate dosing for sulphide control in pressure sewers: case study in Germany. Issue 10 (8th September 2022) - Despot, Daneish; Reinhold, Luisa; Barjenbruch, Matthias
Abstract: Odour release from sewer systems is an established environmental issue affecting many cities worldwide. A key indicator for the severity of the odour problem in sewer systems is linked to the amount of sulphide produced and released as hydrogen sulphide (H2 S) into the urban environment. For this reason, an in-depth understanding of the biochemical processes of sulphurous compounds in sewer systems is an underlying base point for designing and implementing odour control strategies for sewer systems. This contribution focuses on a field study on the monitoring and assessing chemical dosing on a 9.0 km pressure sewer in Ueckermünde, Germany. Online H2 S measurements indicated a daily reoccurrence of sulphide spikes between 4:00 and 8:00 am during the monitoring period. During this period, the wastewater slugs exiting the sewer section remained in the dosed section of the pipe the longest, and regeneration of sulphide production began after 3 hours, causing the hydrogen sulphide spikes. The proposed dosing strategy provides a cost-effective and efficient solution for sulphide build-up in long pressure sewers that connect rural areas to centralised wastewater collection and treatment systems. HIGHLIGHTS: The sulphide problem in the studied sewer system is highly influenced by extremely long retention times leading to the failure of conventional dosing strategies. Using limited downstream nitrate dosing, 1.5–5 mg-N L −1 reduced the H2 S concentration to 0.60–0.26 mg L −1 . The applied dosing strategy provides an effective solution for controlling H2 S sewers typically used to connect rural areas to centralised systems. Graphical Abstract